Factors associated with burnout among minimally invasive gynecologic surgery fellowsAJOG Global Reports at a Glance - Kelli McEntee, MD; Hannah Koenig, MPH; Rohan Hattiangadi, MD; Megan Loring, MD; Amy Brockmeyer, MD; Marisa Dahlman, MD, MPH (Elsevier, 2022)
BACKGROUND: While burnout has been identified in half of practicing physicians, no validated questionnaires have assessed burnout among minimally invasive gynecologic surgery fellows. OBJECTIVE: This study aimed to assess factors associated with burnout among minimally invasive gynecologic surgery fellows. STUDY DESIGN: Cross-sectional online survey including the validated Copenhagen Burnout Inventory: 100 minimally invasive gynecologic surgery fellows in the United States were invited, including the classes of 2021 and 2022. Of the 100 fellows invited, 60 fellows completed the Copenhagen Burnout Inventory survey. Descriptive statistics were used to report the demographic variables, the mean Copenhagen Burnout Inventory score, and the responses to the survey questions. Logistic and linear regression models were created to assess relationships between fellow characteristics and Copenhagen Burnout Inventory scores. RESULTS: Of the 60 fellows with complete Copenhagen Burnout Inventory survey data, 73% were female, 50% were first-year, and 50% were second-year fellows. The mean Copenhagen Burnout Inventory score was 39.2 (standard deviation, 14.4), indicating moderate burnout, and 21.7% of fellows had scores >50, indicating high burnout. Personal and work-related burnout were highest, with Copenhagen Burnout Inventory scores of 47.9 (standard deviation, 16.8) and 45.1 (standard deviation, 17.6), respectively. Patient-related burnout scores were the lowest at 23.5 (standard deviation, 16.5).Factors associated with overall burnout included career choice dissatisfaction (beta, 5.6; 95% confidence interval, 0.9-10.3; P=.02) and absence of a positive and respectful work environment (beta, 5.9; 95% confidence interval, 1.0-10.9; P=.02). Fellows who were somewhat satisfied with their career choice scored 11.2 points higher than those who were highly satisfied. Fellows whose work environment was almost never positive and respectful scored 17.8 points higher than those whose work environment was always positive and respectful. Female fellows were significantly less likely to have a low Copenhagen Burnout Inventory score than male fellows (odds ratio, 0.05; 95% confidence interval, 0.004-0.3; P=.004).Only one-third of fellows reported regular individual wellness behaviors: mindfulness (23%), exercise (35%), 7 to 8 hours of sleep (37%), and recreation (27%); however, these factors were not associated with lower burnout scores. CONCLUSION: Fellows had moderate to high personal and work-related burnout, whereas patient-related burnout was low. Factors associated with burnout were negative work culture, lack of control over work schedule, and decreased career satisfaction. Individual wellness behaviors were not associated with burnout, highlighting the need to look beyond individual behavior in the fight against physician burnout.